PROFIL KIAT MENJAGA KESEHATAN TUBUH DALAM PENCEGAHAN PENULARAN COVID-19 SELAMA MASA PANDEMI PADA WARGA LINGKUNGAN PAULUS MENTENG DALAM, JAKARTA SELATAN DI BULAN MARET-AGUSTUS 2020 - Yovita Harmiatun (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2020)
The effort to prevent transmissing COVID-19 through maintaining the body health of the resident of neighbourhood Paulus Menteng Dalam South Jakarta upon the pandemic of COVID-19 from March until August 2020. The population neighbourhood Paulus Menteng Dalam is 152 persons consist of 80 females and 72 males, and aged about eight until 80 years, 64 are studying and 88 married. In the pandemic COVID-19 from March until August 2020 all of the respondents have done health protocol faithfully. Other efforts to keep the body health: work from home, study from home, pray at home and live streaming at home, and have never done any party. In addition they avoid smoking, alcoholic drink, preventing diabetes melitus, hypertention and heard diseases, by healthy life, with get used to a healthy diet, balanced nutrtion with diversity food, and doing exercice. For preventing stress and hypertention, doing social activity like watching television, WattsApp, telefon call, and regular social gathering on line. The efforts preventing transmission COVID-19 have been done well by the children, that is caused of education, guidance, and encouragement that have been given by their parents. Those were the efforts residents of neighbourhood Paulus Menteng Dalam, stay healthy, saved from transmitting COVID-19, that can be guidance for other people. All of efforts have been done disciplinely, faithfully and with love will produce something positive as be hoped, and can promote public health. Keywords: Covid-s19, healthy life, Paulus Menteng Dalam, health protokol faithfully